HUBUNGAN TINGKAT REFLEKSI KODE ETIK KEDOKTERAN TERHADAP SIKAP DOKTER MUDA DALAM BERKOMUNIKASI KE PASIEN - Mardhatillah Marsa; Nurdiana Putri Roudlotulisa; Dirwan Suryo Soularto (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
The medical code of ethics is a set of professional ethical rules designed to serve as a guideline and deter deviations from the medical profession in Indonesia. Self-reflection, awareness, and comprehension of the values in the medical code of ethics are all forms of reflection on the medical code of ethics. MKDKI had 127 complaints of professional violations as of March 2011, with 80% of the incidents being due to a lack of communication between doctors and patients. The goal of this study is to see if there is a correlation between the reflection level of the medical code of ethics on the attitude of young doctors in communicating with patients. This is a cross-sectional analytic observational study of 80 young FKIK UMY doctors studying professional education in Yogyakarta's Special Region. The Questionnaire of Reflection on the Medical Ethics Code and the Questionnaire of Communicating Attitudes Toward Young Doctors were used to collect data. The Spearman correlation test was used to validate the results. The data analysis results revealed no significant relationship between the reflection of the medical code of ethics on the attitude of young doctors in communicating to patients, with a p value of 0.58. The correlation was weak, despite the positive direction (r = 0.213). There is no correlation between the reflection of the medical code of ethics and young doctors' attitudes about communicating to patients.